Erratum - team, Editorial (Quaestiones Geographicae, 2026)
The Authors apologise for the error in the paper “What doesn’t work in the European co-hesion policy? Development challenges of the inner periphery after the SARS-CoV-2 pandem-ic” by Paweł Churski, Czesław Adamiak, Anna Dubownik, Maciej Pietrzykowski, Barbara Szyda published in Quaestiones Geographicae Vol. 43 No. 4 (2024): 81. https://doi.org/10.14746/quageo-2024-0038